Balanço da emissão de gases carbônicos nas operações florestais e sequestro de carbono em florestas plantadas no Espírito Santo - Carmo, Flávio Cipriano de Assis do (2016)
With the emergence of the Clean Development Mechanism, various forestry companies are being encouraged to develop projects with production techniques that reduce emissions of greenhouse gases, aiming at an increase of income through marketing carbon credits. So aim with this research to quantify the concentration of gases that are emitted during operation of machines and vehicles in forest production activities to achieve a carbon sequestration swing through the forest and the emission during the production process. In this study, both the quantification of gases as opacity. 85 diesel engine machines used in the forestry sector were assessed, responsible for the implementation of forestry activities, forest harvesting, forest transport, administration, protection, construction and maintenance of roads. According to the results obtained in the study, one can conclude that the activity that emits higher quantity of carbon to the atmosphere was forest transport approximately 335 kgC.ha-1 (about 56% of total emission of forestry activities) followed by forest harvesting with 197.91 kgC.ha-1 (32.98% of the total issued), to forestry 53.26 kgC.ha-1 (8.88% of the total issued), construction and maintenance of roads 11.18% (1.86% of the total issued) and activity management and protection had lower emissions per hectare (2.86 kgC.ha-1 - about 0.5% of the total emitido-). For the carbon sheet, it was found that sequesters planted forests around 42 tons per hectare of carbon, and for their development, procurement and transportation of timber 600 is delivered kgC.ha-1 (1.43% of Total kidnapped by the forest). Regarding the issue of opacity, it was found that only 4.71% of the analyzed machines met outside the limits allowed by law (CONAMA 418/09).